2011
DOI: 10.1007/s12663-011-0314-x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Strategies for Treating Compensatory Articulation in Patients with Cleft Palate

Abstract: Introduction Patients with cleft palate (PCP) frequently show compensatory articulation disorder (CAD). Compensatory errors require a prolonged period of speech intervention. Scaffolding strategies are used for correcting placement and manner of articulation. Objective To study whether some strategies commonly used in speech therapy for correcting compensatory articulation errors, can be more effective depending on severity of CAD in PCP. Materials and Methods Fifty PCP were studied. All patients showed veloph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
13

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 20 publications
(21 reference statements)
1
29
0
13
Order By: Relevance
“…) to daily (e.g., Pamplona et al . ), with the majority of studies (55.7%) reporting a dose frequency of two to three times per week. Two studies reported a dose frequency of ‘biweekly’, which was coded as unclear due to the potential for misinterpretation of two times per week or once every 2 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…) to daily (e.g., Pamplona et al . ), with the majority of studies (55.7%) reporting a dose frequency of two to three times per week. Two studies reported a dose frequency of ‘biweekly’, which was coded as unclear due to the potential for misinterpretation of two times per week or once every 2 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…b The number of studies 'reporting no information' about dose includes those that may or may not have reported to include a specific type of dose within the intervention approach (e.g., although not all studies included conceptual intervention, they were coded as not reported). every 6 weeks (e.g., the parent group from experiment 2 in Lancaster et al 2010) to daily (e.g., Pamplona et al 2014), with the majority of studies (55.7%) reporting a dose frequency of two to three times per week. Two studies reported a dose frequency of 'biweekly', which was coded as unclear due to the potential for misinterpretation of two times per week or once every 2 weeks.…”
Section: Intervention Intensitymentioning
confidence: 99%
“…Besides hypernasality and nasal emission, some patients with cleft palate also develop compensatory behaviors known as compensatory articulation errors. These articulation disorders affect intelligibility even more severely than VPI [9].…”
Section: Introductionmentioning
confidence: 99%
“…When present, the CA can make the child's or the adult's speech unintelligible and bring in prejudices to their social lives, studies and even to their professional lives 2,3 . Speech therapy is essential for the establishment of standard production and different intervention approaches have been reported in the literature in order to facilitate typical speech production in this population 4,5 …”
Section: Grant: Pibic-cnpq and Unesp-proexmentioning
confidence: 99%